Review of the genus Epacanthaclisis Okamoto, 1910 in China (Neuroptera: Myrmeleontidae) - Ao, Weiguang; Wan, Xia; Wang, Xinli (Zootaxa, 2010)
Nine antlion species of the genus Epacanthaclisis Okamoto, 1910 from China are reviewed. Two new species, E. amydrovittata Wan et Wang sp. nov. and E. ningshana Wan et Wang sp. nov., are described and illustrated. Epacanthaclisis moiwana (Okamoto, 1905) is newly recorded in China. A key to the species of Epacanthaclisis from China is provided.